Meningkatkan kemampuan pengenalan warna melalui kegiatan eksperimen pelangi pada anak usia 5-6 tahun di TK Azazani - Hikmawati, Aziza Ayu; Susanti, Rikza Azharona (Maliki Interdisciplinary Journal, 2024)
Improving Color Recognition Abilities Through Rainbow Experiment Activities in Children Aged 5-6 Years at Azazani Kindergarten. This research aims to explore the use of experimental methods to improve color recognition abilities in early childhood class B at Azazani Kindergarten. An additional aim is to increase young children’s understanding of color through carrying out rainbow experiments in class B. Recognition of an object does not only depend on its shape, but also includes an understanding of its color which is considered a characteristic of the object. This research involves experimental activities as a way to introduce children directly to colors, thereby allowing them to actively participate in a learning process that is new to them. The aim is to increase children’s interest in learning and also help their cognitive development in recognizing colors. The method applied in this research is Classroom Action Research (PTK) which involves collaboration with the class teacher. The data collection methods used include observation and documentation. The results of the research show that by applying experimental methods, especially by conducting rainbow experiments on glass, the color recognition ability in Azazani Kindergarten can increase. The results of observations in cycle I showed that children were able to recognize colors, group colors and name colors with a success rate of 53.9%, increasing in cycle II to 70.1%.